IMPROVING WHEAT PHOTOSYNTHESIS THROUGH WIDE CROSSING WITH WILD RELATIVES AND SELECTION IN NOVEL ENVIRONMENTS - Briers, LJ (2024)
Climate change poses an immediate threat to wheat yields globally. Already there has been increased incidences of extreme weather events with heatwaves significantly reducing wheat yields in India one of the biggest producers of wheat. In order for wheat yields to meet the increasing global demands there is an urgent need to improve genetic variation in wheat so it is able to tolerate the challenging environment to come. A key target for improving wheat yields is photosynthesis as this is the primary determinant of biomass and therefore yield. Wheat wild relatives are known to exhibit variable photosynthetic traits such as higher assimilation rates under high light and improved RuBisCO kinetics that favour the carboxylation of carbon dioxide over oxygen. There are also reports of bread wheat with wild relative inserts having improved photosynthesis compared to parental lines. In this thesis a set of wheat wild relative crosses known as the ‘Breeder’s toolkit’ lines were evaluated at subambient, ambient and high Ca. The three experiments in this thesis have helped gained a better understanding of the ‘Breeder’s toolkit’ lines responses to different environments. In the first glasshouse experiment an initial screen of physiology and photosynthetic traits was completed to select a subset of variable lines for further characterisation. This study also provided some preliminary data to support the use of 200 ppm Ca as a suitable growth Ca given its evolutionary relevance. In the second experiment the subset of lines were grown at subambient Ca. A large variation was observed in all parameters measured highlighting the value of wild relatives in improving variation in bread wheat. In the final chapter the same subset of lines was grown at ambient and high (~925 ppm) Ca. Interestingly in the ambient Ca grown plants variation was observed in parameters such as gsw and there was found to be a statistically significant impact of wild relative and backcrossing background on gsw. At high Ca measured parameters were not impacted by F1 cross or backcrossing background. This suggests that for this subset of the Breeder' the wild relative insert did not offer an advantage to the plant under high Ca. To summarise wheat wild relatives offer a valuable resource for improved photosynthesis in wheat, however the approach to selecting for these improvements may be environment specific. It will be vital to use a variety of screens for multiple climatic factors elevated CO2, temperature and drought to identify climate proof wheat wild relative introgressions.